Evaluasi Keberhasilan Terapi Anemia Pada Pasien Gagal Ginjal Kronik Di Unit Hemodialisa Rumah Sakit Imanuel Lampung - Mardani, Rusminingtyas Hasri; Nopiyansyah, Nopiyansyah; Lestari, Yovita Endah (Peneliti.net, 2025)
Chronic kidney failure is defined as a decline in chronic kidney function that lasts months to years and is characterized by a decrease in kidney function (Glomerular Filtration Rate) ≤60 ml/min/1.73mm2 and a creatinine albuminuria ratio of ≥ 30mg/g. This study aims to determine the success rate of anemia therapy in patients with Chronic Kidney Failure (CKD) in the Hemodialysis Unit at Imanuel Hospital, Lampung. This research was conducted in March-May 2023. This research is a type of non-experimental research with an analytical descriptive design from medical record data of chronic kidney failure patients undergoing hemodialysis with anemia therapy at Imanuel Lampung Hospital. The patient sample was 41 patients, then data management and data analysis were carried out including HGB and HCT levels. Statistical results using the Paired T-Test obtained a p-value of HGB 0.28 <0.05 and a p-value of HCT 0.110 > 0.05, the Chi Square statistical test obtained a p-value of 0.641 for gender and a p-value a value of 0.734 for comorbidities, the Mann Whitney test obtained a p-value of 0.05 for age. The results of the study Anemia therapy in patients with Chronic Kidney Failure (CKD) at the Hemodialysis Unit at Immanuel Hospital Lampung was successful in 27 patients (66%) and unsuccessful in 14 patients (34%). Patient characteristics such as age, gender, and comorbidities affect the success rate of using anti-anemia drugs in CRF patients at Immanuel Hospital.